Unruly Gods: Divinity and Society in China - Shaḥar, Meʾir; Weller, Robert P. (University of Hawaii Press, 1996)
The first study in English to offer a systematic introduction to the Chinese pantheon of divinities. It challenges received wisdom about Chinese popular religion, which, until now, presented all Chinese deities as mere functionaries and bureaucrats. The essays in this volume eloquently document the existence of other metaphors that allowed Chinese gods to challenge the traditional power structures and traditional mores of Chinese society. The authors draw on a variety of disciplines and methodologies to throw light on various aspects of the Chinese supernatural. The gallery of gods and goddesses surveyed demonstrates that these deities did not reflect China's socio-political order but rather expressed and negotiated tensions within it. In addition to reflecting the existing order, Chinese gods shaped it, transformed it, and compensated for it, and, as such, their work offers fresh perspectives on the relations between divinity and society in China.